STUDENTS’ SCHEMATA ACTIVATION IN EXTENSIVE READING AT STAIN PONOROGO - Andi Susilo, dkk (IAIN PONOROGO, 2013)
This study was aimed at investigating the extent to which the lecturer employed strategy and occupied effective classroom language to assist students’ schemata activation on Extensive Reading class at English DepartmentSTAIN Ponorogo. To meet with the objectives, qualitative case study formed the methodological basis of this present research involving an extensive reading lecturer as the research subject with one of her respective classes consisted of 32 students of fourth semester. The data were derived from lecturer’s utterances (verbal) and body language (nonverbal). Those data were obtained from the transcripts of the recorded lecturer’s utterances during two periods of meeting, and notetaking taken from observations and interviews. The results revealed that the lecturer used to employ questioning technique to activate students’ schemata. Various strategies were predominantly occupied in lecturer’s questioning behaviors to engage students in questionanswer activities, such as probing, redirecting and reinforcement. Generally, those strategies were observed not only to provide motivation and focus students’ attention towards the topic being discussed, but also to give a wide chance of opportunity for them to recall their prior knowledge and ease them to predict the content of reading texts they were going to read. Besides, the language the lecturer used under this investigation was fairly fulfilled the requirements to be communicative as some communicative features of talks were utilized properly, such as referential questions, content feedback, and speech modification to optimize students’ participation and performance in the process of reading.